Spacecraft Water Exposure Guidelines for Selected Contaminants: Volume 3 - National Research Council (The National Academies Press, 2008)
NASA maintains an active interest in the environmental conditions associated with living and working in spacecraft and identifying hazards that might adversely affect the health and well-being of crew members. Despite major engineering advances in controlling the spacecraft environment, some water and air contamination is inevitable. Several hundred chemical species are likely to be found in the closed environment of the spacecraft, and as the frequency, complexity, and duration of human space flight increase, identifying and understanding significant health hazards will become more complicated and more critical for the success of the missions. To protect space crews from contaminants in potable and hygiene water, NASA requested that the National Research Council NRC provide guidance on how to develop water exposure guidelines and subsequently review NASA's development of the exposure guidelines for specific chemicals. This book presents spacecraft water exposure guidelines (SWEGs) for antimony, benzene, ethylene glycol, methanol, methyl ethyl ketone, and propylene glycol.
Keywords: Space and Aeronautics

Methods for Developing Spacecraft Water Exposure Guidelines - National Research Council (The National Academies Press, 2000)
The National Aeronautics and Space Administration (NASA) maintains an active interest in the environmental conditions associated with living and working in spacecraft and identifying hazards that might adversely affect the health and well-being of crew members. Despite major engineering advances in controlling the spacecraft environment, some water and air contamination appears to be inevitable. Several hundred chemical species are likely to be found in the closed environment of the spacecraft, and as the frequency, complexity, and duration of human space flight increase, identifying and understanding significant health hazards will become more complicated and more critical for the success of the missions. NASA asked the National Research Council (NRC) Committee on Toxicology to develop guidelines, similar to those developed by the NRC in 1992 for airborne substances, for examining the likelihood of adverse effects from water contaminants on the health and performance of spacecraft crews. In this report, the Subcommittee on Spacecraft Water Exposure Guidelines (SWEGs) examines what is known about water contaminants in spacecraft, the adequacy of current risk assessment methods, and the toxicologic issues of greatest concern.
Keywords: Space and Aeronautics

Electric Power From Orbit: A Critique of a Satellite Power System (The National Academies Press, 1981)
Keywords: Space and Aeronautics

Guidelines for Developing Spacecraft Maximum Allowable Concentrations for Space Station Contaminants - National Research Council (The National Academies Press, 1992)
Keywords: Space and Aeronautics

Refinements to the Methods for Developing Spacecraft Exposure Guidelines - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Human spaceflight is inherently risky, with numerous potential hazards posed at each phase of a mission. Potential health risks during spaceflights include short-term health consequences from being in microgravity, as well as long-term health consequences that arise, or continue, months or years after a flight. Additional health considerations are risks posed by exposure to environmental contaminants onboard spacecraft. Because the International Space Station and spacecraft are closed environments that require recirculation of air and water supplies, some contamination of the air and water will occur. Even with onboard air and water purification systems, chemicals will accumulate in the air and water as they recirculate or are recycled onboard. Therefore, it is necessary for the National Aeronautics and Space Administration (NASA) to identify hazardous contaminants and determine exposure levels that are not expected to pose a health risk to astronauts.
Keywords: Space and Aeronautics; Environment and Environmental Studies

On NOAA Requirements for Polar-Orbiting Environmental Satellites: Letter Report (The National Academies Press, 1992)
Keywords: Space and Aeronautics

Iodotrifluoromethane: Toxicity Review - National Research Council (The National Academies Press, 2004)
The U.S. military is considering using a compound called iodotrifluoromethane (CF3I) for fire suppression to replace previously-used compounds (halons) that are being phased out because they deplete the ozone layer. This report reviews available toxicological data on CF3I and evaluates the scientific basis of the U.S. Army's proposed exposure limit of 2,000 parts per million (ppm). The report recommends that CF3I be used for fire suppression in normally unoccupied spaces because of its potential to cause cardiac sensitization in test animals. The report also recommends that further genotoxicity testing be conducted (testing for changes in genetic material), and that CF3I be assessed for its potential to cause cancer. Should the Army decide to use CF3I, information should be collected and evaluated on how much of the chemical or any of its degradation products might be released and how often.
Keywords: Environment and Environmental Studies; Space and Aeronautics

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 2 - National Research Council (The National Academies Press, 2002)
This book reviews toxicity documents on five chemicals that can be released in the air from accidents at chemical plants, storage sites, or during transportation. The documents were prepared by the National Advisory Committee on Acute Exposure Guideline Levels for Hazardous Substances and were evaluated for their scientific validity, comprehensives, internal consistency, and conformance to the 1993 guidelines report.
Keywords: Environment and Environmental Studies; Space and Aeronautics

Spacecraft Water Exposure Guidelines for Selected Contaminants: Volume 1 - National Research Council (The National Academies Press, 2004)
To protect space crews from contaminants in potable and hygiene water, NASA requested that the National Research Council (NRC) provide guidance on how to develop water exposure guidelines and subsequently review NASA's development of exposure guidelines for specific chemicals.
Keywords: Space and Aeronautics; Environment and Environmental Studies

Re-evaluation of Drinking-Water Guidelines for Diisopropyl Methylphosphonate - National Research Council (The National Academies Press, 2000)
Diisopropyl Methylphosphonate (DIMP) is a groundwater contaminant at the U.S. Army's Rocky Mountain Arsenal in Colorado. DIMP is a by-product created from the manufacture and detoxification of the nerve agent GB which the arsenal produced from 1953 to 1957. For awhile the Army and the State of Colorado disagreed upon the appropriate drinking-water contaminant guideline for DIMP. A drinking-water guideline of 600 micrograms per liter was established by the U.S. Environmental Protection Agency (EPA) in 1989 but the State of Colorado promulgated a lower guideline of 8 micrograms per liter. The significant difference between the two suggested values arose from the fact that both sides used different studies to determine their values. Colorado used one-generation reproductive toxicity study in mink, whereas EPA used a subchronic toxicity study in dogs. To resolve the disagreement, a two-generation reproductive study in mink was conducted. The Army asked the National Research Council (NRC) to independently evaluate the 1997 study and re-evaluate the drinking-water guideline for DIMP. This task was assigned to the Committee on Toxicology, which established the Subcommittee on the Toxicity of Diisopropyl Methylphosphonate, a multidisciplinary group of experts. The subcommittee evaluated the two-generation reproductive study as well as other studies relevant to the task. Data on the use of mink as a predictive model in toxicology were also reviewed. Re-Evaluation of Drinking-Water Guidelines for Diisopropyl Methylphosphonate is the subcommittee's report which shows that neither party was corrected in their DIMP guidelines. The report includes the subcommittee's evaluation and recommendations concerning the topic.
Keywords: Environment and Environmental Studies; Space and Aeronautics

Spacecraft Maximum Allowable Concentrations for Selected Airborne Contaminants: Volume 5 - National Research Council (The National Academies Press, 2008)
NASA is aware of the potential toxicologic hazards to crew that might be associated with prolonged spacecraft missions. Despite major engineering advances in controlling the atmosphere within spacecraft, some contamination of the air appears inevitable. NASA has measured numerous airborne contaminants during space missions. As the missions increase in duration and complexity, ensuring the health and well-being of astronauts traveling and working in this unique environment becomes increasingly difficult. As part of its efforts to promote safe conditions aboard spacecraft, NASA requested the National Research Council to develop guidelines for establishing spacecraft maximum allowable concentrations (SMACs) for contaminants and to review SMACs for various spacecraft contaminants to determine whether NASA's recommended exposure limits are consistent with the guidelines recommended by the committee. This book is the fifth volume in the series Spacecraft Maximum Allowable Concentrations for Selected Airborne Contaminants, and presents SMACs for acrolein, C3 to C8 aliphatic saturated aldehydes, C2 to C9 alkanes, ammonia, benzene, carbon dioxide, carbon monoxide, 1,2-dichloroethane, dimethylhydrazine, ethanol, formaldehyde, limonene, methanol, methylene dichloride, n-butanol, propylene glycol, toluene, trimethylsilanol, and xylenes.
Keywords: Space and Aeronautics; Environment and Environmental Studies

Spacecraft Water Exposure Guidelines for Selected Contaminants: Volume 2 - National Research Council (The National Academies Press, 2007)
The International Space Station is a closed and complex environment, so some contamination of its internal atmosphere and water system is expected. To protect space crews from contaminants in potable and hygiene water, the National Aeronautics and Space Administration (NASA) requested that the National Research Council (NRC) provide guidance on how to develop water exposure guidelines and review NASA's development of the exposure guidelines for specific chemicals. NASA selects water contaminants for which spacecraft water exposure guidelines (SWEGs) will be established; this involves identifying toxicity effects relevant to astronauts and calculating exposure concentrations on the basis of those end points. SWEGs are established for exposures of 1, 10, 100, and 1,000 days. This report is the second volume in the series, Spacecraft Water Exposure Guidelines for Selected Chemicals. SWEG reports for acetone, alkylamines, ammonia, barium, cadmium, caprolactam, formate, formaldehyde, manganese, total organic carbon, and zinc are included in this report. The committee concludes that the SWEGs developed for these chemicals are scientifically valid based on the data reviewed by NASA and are consistent with the NRC (2000) report, Methods for Developing Spacecraft Water Exposure Guidelines. SWEG reports for additional chemicals will be presented in a subsequent volume.
Keywords: Space and Aeronautics; Environment and Environmental Studies

Methyl Bromide Risk Characterization in California - National Research Council (The National Academies Press, 2000)
Methyl bromide is gaseous pesticide used to fumigate soil, crops, commodity warehouses, and commodity-shipping facilities. Up to 17 million pounds of methyl bromide are used annually in California to treat grapes, almonds, strawberries, and other crops. Methyl bromide is also a known stratospheric ozone depleter and, as such, is scheduled to be phased out of use in the United States by 2005 under the United Nations Montreal Protocol. In California, the use of methyl bromide is regulated by the Department of Pesticide Regulation (DPR), which is responsible for establishing the permit conditions that govern the application of methyl bromide for pest control. The actual permits for use are issued on a site-specific basis by the local county agricultural commissioners. Because of concern for potential adverse health effects, in 1999 DPR developed a draft risk characterization document for inhalation exposure to methyl bromide. The DPR document is intended to support new regulations regarding the agricultural use of this pesticide. The proposed regulations encompass changes to protect children in nearby schools, establish minimum buffer zones around application sites, require notification of nearby residents, and set new limits on hours that fumigation employees may work. The State of California requires that DPR arrange for an external peer review of the scientific basis for all regulations. To this end, the National Research Council (NRC) was asked to review independently the draft risk characterization document prepared by DPR for inhalation exposure to methyl bromide. The task given to NRC's subcommittee on methyl bromide states the following: The subcommittee will perform an independent scientific review of the California Environmental Protection Agency's risk assessment document on methyl bromide. The subcommittee will (1) determine whether all relevant data were considered, (2) determine the appropriateness of the critical studies, (3) consider the mode of action of methyl bromide and its implications in risk assessment, and (4) determine the appropriateness of the exposure assessment and mathematical models used. The subcommittee will also identify data gaps and make recommendations for further research relevant to setting exposure limits for methyl bromide. This report evaluates the toxicological and exposure data on methyl bromide that characterize risks at current exposure levels for field workers and nearby residents. The remainder of this report contains the subcommittee's analysis of DPR's risk characterization for methyl bromide. In Chapter 2, the critical toxicological studies and endpoints identified in the DPR document are evaluated. Chapter 3 summarizes DPR's exposure assessment, and the data quality and modeling techniques employed in its assessment are critiqued. Chapter 4 provides a review of DPR's risk assessment, including the adequacy of the toxicological database DPR used for hazard identification, an analysis of the margin-of-exposure data, and appropriateness of uncertainty factors used by DPR. Chapter 5 contains the subcommittee's conclusions about DPR's risk characterization, highlights data gaps, and makes recommendations for future research.
Keywords: Environment and Environmental Studies; Space and Aeronautics

Copper in Drinking Water - National Research Council (The National Academies Press, 2000)
The safety of the nation's drinking water must be maintained to ensure the health of the public. The U.S. Environmental Protection Agency (EPA) is responsible for regulating the levels of substances in the drinking water supply. Copper can leach into drinking water from the pipes in the distribution system, and the allowable levels are regulated by the EPA. The regulation of copper, however, is complicated by the fact that it is both necessary to the normal functioning of the body and toxic to the body at too high a level. The National Research Council was requested to form a committee to review the scientific validity of the EPA's maximum contaminant level goal for copper in drinking water. Copper in Drinking Water outlines the findings of the committee's review. The book provides a review of the toxicity of copper as well as a discussion of the essential nature of this metal. The risks posed by both short-term and long-term exposure to copper are characterized, and the implications for public health are discussed. This book is a valuable reference for individuals involved in the regulation of water supplies and individuals interested in issues surrounding this metal.
Keywords: Environment and Environmental Studies; Space and Aeronautics

Toxicological Risks of Selected Flame-Retardant Chemicals - National Research Council (The National Academies Press, 2000)
Ignition of upholstered furniture by small open flames from matches, cigarette lighters, and candles is one of the leading causes of residential-fire deaths in the United States. These fires accounted for about 16% of civilian fire deaths in 1996. On average, each year since 1990, about 90 deaths (primarily of children), 440 injuries, and property losses amounting to 50 million dollars have resulted from fires caused by the ignition of upholstered furniture by small open flames. Certain commercial seating products (such as aircraft and bus seats) are subject to flammability standards and sometimes incorporate FR-treated upholstery cover materials, but there is no federal-government requirement for residential upholstered furniture, and it is generally not treated with FR chemicals. It is estimated that less than 0.2% of all U.S. residential upholstery fabric is treated with flame-retardant (FR) chemicals. The Consumer Product Safety Act of 1972 created the U.S. Consumer Product Safety Commission (CPSC) as an independent federal regulatory agency whose mission is to protect the public from unreasonable risks of injury and death associated with consumer products. CPSC also administers the Flammable Fabrics Act, under which it regulates flammability hazards and the Federal Hazardous Substances Act (FHSA), which regulates hazardous substances including chemicals. In 1993, the National Association of State Fire Marshals petitioned CPSC to issue a performance-based flammability standard for upholstered furniture to reduce the risk of residential fires. The Commission granted that portion of the petition relating to small open flame ignition risks. In response to concerns regarding the safety of FR chemicals, Congress, in the fiscal year 1999 appropriations report for CPSC, requested that the National Research Council conduct an independent study of the health risks to consumers posed by exposure to FR chemicals that are likely to be used in residential upholstered furniture to meet a CPSC standard. The National Research Council assigned the project to the Committee on Toxicology (COT) of the Commission on Life Sciences' Board on Environmental Studies and Toxicology. COT convened the Subcommittee on Flame-Retardant Chemicals, which prepared this report. Subcommittee members were chosen for their recognized expertise in toxicology, pharmacology, epidemiology, chemistry, exposure assessment, risk assessment, and biostatistics. Toxicological Risks of Selected Flame-Retardant Chemicals is organized into 18 chapters and two appendices. Chapter 2 describes the risk assessment process used by the subcommittee in determining the risk associated with potential exposure to the various FR chemicals. Chapter 3 describes the method the subcommittee used to measure and estimate the intensity, frequency, extent, and duration of human exposure to FR chemicals. Chapters 4-19 provide the subcommittee's review and assessment of health risks posed by exposure to each of the 16 FR chemicals. Data gaps and research needs are provided at the end of these chapters.
Keywords: Environment and Environmental Studies; Space and Aeronautics

Ensuring the Climate Record from the NPP and NPOESS Meteorological Satellites (The National Academies Press, 2000)
Keywords: Space and Aeronautics; Environment and Environmental Studies

Commercial Aircraft Propulsion and Energy Systems Research: Reducing Global Carbon Emissions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The primary human activities that release carbon dioxide (CO2) into the atmosphere are the combustion of fossil fuels (coal, natural gas, and oil) to generate electricity, the provision of energy for transportation, and as a consequence of some industrial processes. Although aviation CO2 emissions only make up approximately 2.0 to 2.5 percent of total global annual CO2 emissions, research to reduce CO2 emissions is urgent because (1) such reductions may be legislated even as commercial air travel grows, (2) because it takes new technology a long time to propagate into and through the aviation fleet, and (3) because of the ongoing impact of global CO2 emissions.
Keywords: Space and Aeronautics; Environment and Environmental Studies

Global Navigation Satellite Systems: Report of a Joint Workshop of the National Academy of Engineering and the Chinese Academy of Engineering - National Academy of Engineering (The National Academies Press, 2012)
The Global Positioning System (GPS) has revolutionized the measurement of position, velocity, and time. It has rapidly evolved into a worldwide utility with more than a billion receiver sets currently in use that provide enormous benefits to humanity: improved safety of life, increased productivity, and wide-spread convenience. Global Navigation Satellite Systems summarizes the joint workshop on Global Navigation Satellite Systems held jointly by the U.S. National Academy of Engineering and the Chinese Academy of Engineering on May 24-25, 2011 at Hongqiao Guest Hotel in Shanghai, China. "We have one world, and only one set of global resources. It is important to work together on satellite navigation. Competing and cooperation is like Yin and Yang. They need to be balanced," stated Dr. Charles M. Vest, President of the National Academy of Engineering, in the workshop's opening remarks. Global Navigation Satellite Systems covers the objectives of the workshop, which explore issues of enhanced interoperability and interchangeability for all civil users aimed to consider collaborative efforts for countering the global threat of inadvertent or illegal interference to GNSS signals, promotes new applications for GNSS, emphasizing productivity, safety, and environmental protection. The workshop featured presentations chosen based on the following criteria: they must have relevant engineering/technical content or usefulness; be of mutual interest; offer the opportunity for enhancing GNSS availability, accuracy, integrity, and/or continuity; and offer the possibility of recommendations for further actions and discussions. Global Navigation Satellite Systems is an essential report for engineers, workshop attendees, policy makers, educators, and relevant government agencies.
Keywords: Engineering and Technology; Space and Aeronautics

Spacecraft Maximum Allowable Concentrations for Selected Airborne Contaminants: Volume 4 - National Research Council (The National Academies Press, 2000)
The National Aeronautics and Space Administration (NASA) is aware of the potential toxicological hazards to crew members that might be associated with prolonged spacecraft missions. Despite major engineering advances in controlling the atmosphere within spacecraft, some contamination of the air appears inevitable. NASA has measured numerous airborne contaminants during space missions. As the missions increase in duration and complexity, ensuring the health and well-being of astronauts traveling and working in this unique environment becomes increasingly difficult. As part of its efforts to promote safe conditions aboard spacecraft, NASA requested the National Research Council (NRC) to develop guidelines for establishing spacecraft maximum allowable concentrations (SMACs) for contaminants, and to review SMACs for various spacecraft contaminants to determine whether NASA's recommended exposure limits are consistent with the guidelines recommended by the subcommittee. In response to this request, the NRC first developed criteria and methods for preparing SMACs for spacecraft contaminants, published in its 1992 report Guidelines for Developing Spacecraft Maximum Allowable Concentrations for Space Station Contaminants. Since then, the NRC's Subcommittee on Spacecraft Maximum Allowable Concentrations has been reviewing NASA's documentation of chemical-specific SMACs. This report is the fourth volume in the series Spacecraft Maximum Allowable Concentrations for Space Station Contaminants. The first volume was published in 1994 and the second and third in 1996. Spacecraft Maximum Allowable Concentrations for Selected Airborne Contaminants: Volume 4 has been reviewed in draft form by individuals chosen for their technical expertise and diverse perspectives in accordance with procedures approved by the NRC's Report Review Committee for reviewing NRC and Institute of Medicine reports. The purpose of that Independent review was to provide candid and critical comments to assist the NRC in making the published report as sound as possible and to ensure that the report meets institutional standards for objectivity, evidence, and responsiveness to the study charge. The review comments and draft manuscript remain confidential to protect the integrity of the deliberative process.
Keywords: Space and Aeronautics; Environment and Environmental Studies

Toxicological Effects of Methylmercury - National Research Council (The National Academies Press, 2000)
Mercury is widespread in our environment. Methylmercury, one organic form of mercury, can accumulate up the aquatic food chain and lead to high concentrations in predatory fish. When consumed by humans, contaminated fish represent a public health risk. Combustion processes, especially coal-fired power plants, are major sources of mercury contamination in the environment. The U.S. Environmental Protection Agency (EPA) is considering regulating mercury emissions from those plants. Toxicological Effects of Methylmercury reviews the health effects of methylmercury and discusses the estimation of mercury exposure from measured biomarkers, how differences between individuals affect mercury toxicity, and appropriate statistical methods for analysis of the data and thoroughly compares the epidemiological studies available on methylmercury. Included are discussions of current mercury levels on public health and a delineation of the scientific aspects and policy decisions involved in the regulation of mercury. This report is a valuable resource for individuals interested in the public health effects and regulation of mercury. The report also provides an excellent example of the implications of decisions in the risk assessment process for a larger audience.
Keywords: Environment and Environmental Studies; Space and Aeronautics